Remodeling of phospholipid composition in colon cancer cells by 1α, 25(OH)2D3 and its analogs. Issue 148 (April 2015) - Leyssens, Carlien; Marien, Eyra; Verlinden, Lieve; Derua, Rita; Waelkens, Etienne; Swinnen, Johannes V.; Verstuyf, Annemieke
Highlights: 1, 25(OH)2 D3 and its analogs modulated the lipid profile of human colon cancer cells. 1, 25(OH)2 D3 and its analogs affected lipogenic gene expression in these cells. Analogs mostly induced similar and more pronounced changes compared to 1, 25(OH)2 D3 . Changes in lipid profile after 1, 25(OH)2 D3 /analog treatment were cell-line dependent. Abstract: Alterations in cellular phospholipid composition are emerging as important traits in the development and progression of cancer. In this study we investigated the effects of 1α, 25-dihydroxyvitamin D3 [1, 25(OH)2 D3 ] and two of its more antiproliferative analogs on the cellular phospholipid composition of various human colon cancer cell lines. Treatment of Caco-2, SW1417 and SW480-ADH cells with 3 × 10 −8 M 1, 25(OH)2 D3, CD578 or WU515 evoked significant changes in phospholipid composition, with the analogs being more potent than the natural compound. Observed effects included changes in acyl chain elongation and acyl chain saturation, and were substantially different in the various cell lines. Consistent with the alterations in phospholipid profiles, 1, 25(OH)2 D3 and its analogs provoked changes in several lipogenic enzymes such as fatty acid synthase (FASN), acetyl-CoA carboxylase (ACACA) and fatty acid elongases (ELOVLs). These effects were also cell line dependent. Taken together these findings indicate that 1, 25(OH)2 D3 and its analogs have divergent effects on the phospholipid composition of different colon cancer cell lines and warrant further investigation of the effect of 1, 25(OH)2 D3 and its analogs on lipid metabolism in various subtypes of primary human colon cancers.